Sustainable pork production and processing: a step toward empowering tribal women in Northeast India - Mehta, Shivani; Bhattacharjee, Mahua (Frontiers in Nutrition, 2024)
This study explores the transformative potential of sustainable pork production and processing as a tool to empower tribal women in the northeast region (NER) of India. The NER is faced with multiple challenges, such as poverty, gender inequality, and poor livelihood methods. Therefore, enhancing sustainable production and processing methods for pork, which is their staple food, presents not only an opportunity for the socio-economic development of the region but also an effective tool for the economic empowerment of tribal women. Through a primary survey of pork value chain actors in Assam, Meghalaya, and Nagaland (the largest producers and consumers of pork in the NER), the study outlines the current practices and barriers to sustainable pork production methods. Although the consumption of pork has remained unchanged and that of processed pork items is on the rise, the production of pork is drastically declining. Therefore, reviving pork production in the NER can be instrumental in building sustainable livelihood models, especially for tribal women in the region. The study explores the effectiveness of a community-based, ‘model village approach,’ where capacity building around sustainable pork production, processing, and waste management techniques results in the economic empowerment of women. The findings from the post-impact analysis of the capacity-building approach call for policy intervention and the establishment of supportive networks to enhance the growth of a sustainable pork production system across NER, thereby contributing to the attainment of Sustainable Development Goal (SDG) targets proposed by the Indian economy.